Uuderstanding Local Process: Contemplating Franchisation - Jones, Colin (Journal of Entrepreneurship, Business and Economics; Vol 1 No 1/2 (2013), 2013)
Purpose- Increasing, there is growing acknowledgement of the importance of franchising within all modern global economies. Despite this, little is understood with regards the actual impact of franchis-ing on local economies. This research aims to reframe the contribution of franchising by considering the process of franchisation. Design/methodology/approach- This study employed a mixed-method approach, utilizing critical realism to facilitate an outcomes-based explanation of firm survival. The focus of the study was upon generative mechanisms that were assumed to give rise to particular events from which (pizza) firm survival was enhanced vis-à-vis all other community members. A database of 2440 firms (or in excess of 21,000 company years) combined with archival records, interviews and the researcher’s observa-tions provided the researcher with access to the nature of interaction occurring between firms. Findings- It was found that the survival of local firms was influenced positively by the day-to-day actions of franchise operators. However, it is argued that to understand how any such advantage my fall to local independent firms, we need too better appreciate the multitude of local processes related to such industries. Originality/value- This research re-examines several ecological concepts with the view of enabling a clearer investigation of underlying local processes. It also represents an authentic autecological ap-proach to the study of firms. Case Study Reference to this paper should be made as follows: Jones, C (2013). “Uuderstanding Local Process: Contemplating Franchisation”, Journal of Entrepreneurship, Business and Economics, Vol. 1 No. 1/2, pp. 1–16.